Solve for K by simplifying both sides of the equation, then isolate the variable.
K = 193
Answer: -3x^3 - 7x^2 - x + 39
Step-by-step explanation:
2/(x^2 -9) - 3x/(x^2-5x+6)
get those denominators factored out
2/(x-3)(x+3) - 3x/(x-3)(x-2)
Multiply both by both denominators
2(x-3)(x-2) - 3x(x-3)(x+3)
Multiply it out
(2x^2 - 10x + 12) - (3x^3 + 9x^2 -9x - 27)
Simplify and it becomes
-3x^3 -7x^2 -x + 39
3y = x - 1...I am going to re-arrange this.....-x + 3y = -1
-x + 3y = -1
x - 2y = 2
---------------add...u will notice that the x's cancel
y = 1
3y = x - 1
3(1) = x - 1
3 = x - 1
3 + 1 = x
4 = x
solution is (4,1)